Sinergi Pemanfaatan Teknologi dan Kreativitas Dosen dalam Meningkatkan Motivasi Belajar Mahasiswa di Era Digital - Jibrael Mau; Anggita Vanesa Liunima; Aurelia Rhiny Zaprila Liha; Arina Maria Nahak; Kresensia Asmy Harut (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2026)
Low learning motivation is one of the educational problems that affects the quality of learning and student learning outcomes. To overcome this, synergy is needed between the use of technology and the creativity of lecturers so that learning is more optimal. To examine the above problems in more depth, this research applies a quantitative approach through a survey method. The population in this study includes all students from 6 PTN in (NTT), with a sampling method using probability sampling techniques and an incidental approach. Before the regression analysis was carried out, an instrument test was first carried out which showed that all statements were valid, consisting of 10 items for variable X1, 15 items for X2, and 15 items for Y. Furthermore, a multiple linear regression analysis was carried out which began with a prerequisite test, and the results showed that all data met the eligibility requirements. After that, it was continued with multiple linear regression analysis and hypothesis testing. The results of the analysis showed that variable X1 had a positive but insignificant effect on variable Y, while variable